Ovarian Fetiform Teratoma in 38 Years Nulliparous Woman: A Case Report - Desalew Gedamu; Mekitie Wondafrash; Meron Berhanu (Clinical Case Reports)
ABSTRACT Fetiform teratoma, another name for homunculus, is a rare form of mature teratoma that is highly differentiated and has parts that resemble a malformed fetus. We reported a case of ovarian Fetiform teratoma in a 38 years old nulliparous woman presented with right side abdominal distention of 10 years duration. An ultrasound revealed a heterogeneous pelvic cystic mass that ranged in appearance from fully hyperechoic to fully hypoechoic, suggesting mature cystic teratoma. The patient underwent laparotomy. Histopathology of Cystectomy specimen was found to be compatible with Fetiform teratoma. It is important to distinguish this highly differentiated benign neoplasm with potential somatic malignant transformation from Fetus in fetu and ectopic pregnancy. To establish the diagnosis, a thorough clinicopathologic examination, laboratory tests for pregnancy and relevant cytogenetic tests for Zygosity should be performed.